2021
DOI: 10.3389/fmicb.2021.772007
|View full text |Cite
|
Sign up to set email alerts
|

Postdiagenetic Bacterial Transformation of Nickel and Vanadyl Sedimentary Porphyrins of Organic-Rich Shale Rock (Fore-Sudetic Monocline, Poland)

Abstract: Nickel and vanadyl porphyrins belong to the so-called fossil geo- or sedimentary porphyrins. They occur in different types of organic matter-rich sediments but mostly occur in crude oils and their source rocks, oil shales, coals, and oil sands. In this study, we aimed to understand the process of bacterial transformation of geoporphyrins occurring in the subsurface shale rock (Fore-Sudetic Monocline, SW Poland). We studied these transformations in rock samples directly obtained from the field; in rock samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Vanadyl-cycloalkano-porphyrins [9] Etio and DPEP iron porphyrins [10] Etio,DPEP benzo-etio and benzo-DPEP vanadyl porphyrins Vanadyl porphyrins of series etio/DPEP [11] Octaethyl nickel porphyrin [12] Octaethyl vanadyl porphyrin Meso-tetraphenyl vanadyl porphyrin Meso-tetraphenyl nickel porphyrin…”
Section: Iron Benz-cycloalkanoporphyrinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vanadyl-cycloalkano-porphyrins [9] Etio and DPEP iron porphyrins [10] Etio,DPEP benzo-etio and benzo-DPEP vanadyl porphyrins Vanadyl porphyrins of series etio/DPEP [11] Octaethyl nickel porphyrin [12] Octaethyl vanadyl porphyrin Meso-tetraphenyl vanadyl porphyrin Meso-tetraphenyl nickel porphyrin…”
Section: Iron Benz-cycloalkanoporphyrinsmentioning
confidence: 99%
“…Previous studies have shown that bacteria degrades or cleaves aliphatic and aromatic substituents of nickel and vanadyl geoporphyrins, leading to the formation of modified geoporphyrins, and also degrades the tetrapyrrole ring. The end products observed due to the microbial activity on shale rock are mono-, di-, and tripyrrole compounds [12]. Table 1 shows the list of modified geoporphyrins and pyrrole compounds identified in the shale rock inhabited by bacteria.…”
Section: Introductionmentioning
confidence: 99%